Sigortacılıkta kara para ile mücadele - Şentürk, Şenol Serkan (My University, 2009)
Tezin birinci bölümünde genel olarak kara para ile ne kastedildiği anlatılmakta, uluslar arası sözleşmelerden faydalanılarak kara paranın tanımı yapılmaktadır. Kara para aklamanın aşamaları, tahmini olarak dünyada bir yıl içerisinde aklanan kara para tutarı, kara paraya yaygın olarak ne gibi suçların öncüllük ettiği, ne gibi kara para aklama yöntemlerinin kullanıldığı ve kara paranın hem ekonomide hem de toplumda yol açtığı tahribatlar ana hatlarıyla incelenmektedir. İkinci bölümde sigorta sektörü ve kara para birlikte incelenmektedir. Bu bölümde öncelikle sigortacılık hakkında kısa bir bilgi verilmekte, sigorta sektörünün yapısı ve başlıca sigorta ürünleri üzerinde durulmaktadır. Dünya ve Türkiye sigorta piyasalarının büyüklükleri verilerek sektörün kara para için oluşturabileceği potansiyel daha somut bir taban üzerine oturtulmaya çalışılmıştır. Sigortacılığın uluslar arası niteliğinin olması, piyasanın sigorta şirketleri, reasürörler, sigorta aracıları gibi çok sayıda farklı unsurdan oluşması, sigorta ürünlerinin sofistike niteliği, özellikle bazı hayat sigortası ürünlerinin değer saklama ve transfer edilebilme özellikleri taşıması kara para aklayıcıların ilgisinin bu sektöre yönelmesi sonucunu doğurmaktadır. Üçüncü bölümde kara para aklanmasına karşı hem genel hem de sigorta sektörü özelinde ne gibi önlemler alındığı, ne tür organizasyonlar oluşturulduğu hem ulusal hem de uluslar arası bazda incelenmektedir. Uluslar arası bazda Mali Eylem Görev Gücü (FATF) ve Uluslar Arası Sigorta Denetçileri Birliği (IAIS), ulusal bazda ise Mali Suçlar Araştırma Kurulu (MASAK)’nun çalışmalarına dayanılarak kara para aklayıcılara karşı neler yapıldığı ve yapılabileceği üzerinde durulmaktadır.

Money laundering is the practice of disguising illegally obtained funds so that they seem legal. The money laundered increases power of crime organizations in societies and economies, which causes to spread corruption, feeds roots of crime, overall has bad effect both on economy and social order. Developed countries has been aware of destroying affects of dirty money. That’s why, they have taken counter measures and established institutions both individually and internationally. As they take measures and make strict regulations against money laundering, for cleaning dirty money money launderers seek different ways, industries more sophisticated and less regulated, and also countries with loose money laundering regulations. Insurance industry has sophisticated insurance products that everybody can’t have an idea easily, wide premium distribution channels from agents to brokers, and also international dimension because of reinsurance. Additionally, it is less regulated than banking industry regarding money laundering. Turkey is a developing country and still follows developed countries by adapting their regulations. That’s why, it is always slow to take measures against negative developments in economic and social life. In respect of money laundering, Turkey is following the same way. It has still loops in money laundering regulations, and mostly it is late to take measures in time. Because of the reasons mentioned above, both Turkey and its insurance industry could be a potential target of money launderers. However, there are not many researches about money laundering in insurance industry in Turkey. Mostly researchers tend to study on the banking industry because of its relatively huge part in the Turkish economy. With that thesis, I tried to make contribution to the efforts against to money laundering in Turkish insurance industry.
Keywords: Bankalar ve Bankacılık; Kara Para; Sigortacılık